Teenage Identity in the Face of the Other in Nnedi Okorafor’s Organic Fantasy - Drab, Ewa (Romanica Silesiana, 2021)
The present paper aims at discussing What Sunny Saw in the Flames by Nnedi Okorafor as a fantasy novel for children and young adults focused upon the question of self-identification. In the framework of fiction for younger audiences, the fantasy mode becomes a tool which allows to examine the topics important to young readers, such as identity and their place within the society, by providing a confrontation with the Other. The example of Nnedi Okorafor’s book, known in the USA as Akata Witch, shows how the instrumentation of a fantasy novel enables an exposition of the process in which the protagonist grows on the intellectual, emotional and cultural levels. In other words, the fantasy mode aids in the exploration of Sunny’s American-Nigerian origin, her albinism, coming of age and the comprehension of her identity. Simultaneously, as additional topics emerge from the analysis, it becomes visible that the question of the Self cannot be separated from the concept of the Other, with the lesson of empathy and respect for what is different.